TRANSITIONS AND CHANGES IN GLOBAL GEOSTRATEGIC POWER BALANCE - Boldbaatar Zagdsuren, (International Journal of Innovative Technologies in Social Science, 2024)
Today, global political relations are experiencing significant changes. The distribution of geostrategic power is influenced by various factors such as competition among nations, economic strength, and military capabilities. Major countries, both central and regional, are pursuing their strategic interests and working towards establishing a new international relations model. As the dynamics between the United States, China, Russia, and other key players evolve, a new geopolitical landscape is taking shape, leading to substantial shifts in international security and order. This research delves into the evolving global geostrategic power balance, examining its key trends, underlying causes, and potential outcomes. It scrutinizes the current state of international relations, and the strategic policies adopted by countries on regional and global scales, and offers insights into future developments.